Breaking my silence as a 'trained' dancer in post-apartheid South Africa - Jones, Danielle-Marie (Department of Drama, 2020)
This research is a personal reflection and a self-study of two performances that have taken place over the course of two years. My Medium Project titled, When Memories Break, set out to navigate ways of decolonising oppressive dominance and investigating the ramifications of indoctrination in dance. In 2017, during my Honours Degree in Dance Studies at the University of Cape Town, I created a poster-painting with a fellow #FeesMustFall artist-activist. This poster-painting, entitled, Amputation, was introduced at UCT School of Dance' Confluences 9: Deciphering decolonisation in Dance Pedagogy in the 21st Century in Cape Town, South Africa. Since then, Amputation has become a personal credo that I have carried with me in my Practice as Research field of study. In 2018, as part of my Minor Project, I not only highlighted my memories and experiences in Classical Ballet, but also included my memories of other informal1 dance influences. The purpose of this essay is therefore not to depict ballet as a current colonialist art form but rather to draw attention to what it represented during the years of colonialism, apartheid, and the aftermath of that. It is against this background that I explore the issues related to the relationship I have with my dance training to date. As a performer-researcher, I will use my living experience as a case study. This article provides a perspective from a performer-researcher's position using selfreflexivity as a research methodology. My conclusion supports the notion that self-reflection in the quest for decolonisation in dance by performer-researchers is important for the evolution of a more democratic society.